Optimalisasi Sosial Media Sebagai Media Pemasaran Usaha Kecil Menengah - Tito Siswanto (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2013)
Communication is a very important element in marketing, because marketing is essentially the communication between producers and consumers. The more advanced development of technology and information, it encourages the changes of conventional communications to modern communication which is digital life style. To support the realization of such communication, the internet became an important element in the creation of modern marketing communications. Until finally, comes the online social media that offers ease of marketing communications with the online system. Because of their low cost and ease of access, it is not un-common these media are conducted by the company in marketing their products. This article will explore the importance of social media for small and medium enterprises as an effort to improve the company's competitive.